1998
DOI: 10.1542/peds.102.s3.507
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Normal Puberty

Abstract: We reviewed the growth characteristics of American boys and girls from published studies, including age at takeoff, age at peak height velocity, peak height velocity, duration of puberty, and the magnitude of the pubertal contribution to adult height. Age at takeoff is highly variable and sex-dependent. The mean takeoff age in children growing at an average rate is ∼11 years in boys and 9 years in girls, and peak height velocity occurs at a mean age of 13.5 years and 11.5 years, respectively, in these children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(44 citation statements)
references
References 11 publications
2
41
1
Order By: Relevance
“…This confirms that children from the canton of Zurich are on average taller than the WHO reference population [34]. Previous studies reported a slightly higher age of peak height growth in Switzerland (13.9 years for males; 12.2 years for females) than the UK (13.6 years for males; 11.7 years for females), Canada (13.4 years for males; 11.8 years for females), and the United States (13 years for males, 11 years for females) [35][36][37].…”
Section: Comparison With Other Studiesmentioning
confidence: 89%
“…This confirms that children from the canton of Zurich are on average taller than the WHO reference population [34]. Previous studies reported a slightly higher age of peak height growth in Switzerland (13.9 years for males; 12.2 years for females) than the UK (13.6 years for males; 11.7 years for females), Canada (13.4 years for males; 11.8 years for females), and the United States (13 years for males, 11 years for females) [35][36][37].…”
Section: Comparison With Other Studiesmentioning
confidence: 89%
“…Fellows will need to understand growth, dietary intake, and physical activity patterns/capacity from a developmental perspective. For example, peak times for growth (height and weight) occur during the first 2 years of life (Wilmore & Costill, 1994) and then during adolescence (Abbassi, 1998). For dietary intake, developmental variations in growth affect caloric needs and help to guide prevention and intervention strategies.…”
Section: Core Competency: Scientific Knowledge and Methodsmentioning
confidence: 99%
“…The most recognizable physical and biological signs during puberty are statural growth (approximately 20% of adult stature matures during puberty) and the acquisition of secondary sexual characteristics [19]. The most widely employed staging system is that of sexual maturity assessments, also referred to as "Tanner stages", initially proposed by Marshall and Tanner [20,21].…”
Section: Physiology Of Pubertymentioning
confidence: 99%